Implementation of Integrated Sub-District Administrative Service Policy in Garut District - Lia Febrianti (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
The purpose of this study was to analyze and describe about the implementation, determine the obstacles and determine the strategies to face the obstacles from policy implementation of PATEN in improving of service quality in Balubur Limbangan district. For this study, the author uses qualitative method with case study approach. To collect the data, the author implements the method of interview, documentation, and passive participation observation. Besides that, analyzing data technique with triangulation and Strengths, Weakness, Opportunities and Threads Analysis as well as Litmus Test is also used. This study resulted several important findings such as 1) Standard and objective, there are still have shortcomings in the fulfillment of administrative requirements. It is all because the absent of Regent Regulations which concern about service standard and Regent Regulations about description of personal district assignment in order of PATEN implementation; 2) Resources the existing funds are still inadequate for the fulfillment of quality facilities and infrastructure, as well as inadequate quality and quantity of district personnel; 3) Economic, social and political condition, there are public awareness still low in the management of licensing services; 4) The disposition of implementers, showed the community still complains about the attitude of the district official and the information on the timeliness of completion of service files. Therefore, beside the broad authority according to its portion, district also needs to be supported by the funding, facilities and infrastructure, and the adequate of both quality and quantity of district official.